Pengaruh Pupuk Hayati Berbasis Jamur Mikoriza Arbuskular dan Rhizobakteri Pemacu Pertumbuhan Tanaman terhadap Pertumbuhan Bibit Kakao (Theobroma cocoa L.) - Tiwit Widowati; Tirta Kumala Dewi; Sylvia Josephine Ruth Lekatompessy; Sarjiya Antonius (Politeknik Negeri Lampung, 2020)
One effort to improve quality of cocoa seedlings is application of bio fertilizer during the nursery. Nutrient supply is essential for growth and development of cocoa seedlings at nursery and field after transplanting. The aim of this research is to determine effect of bio fertilizer application to growth of cocoa seedlings. The study used a completetly randomized design with 4 treatments and 15 replications. The treatments were no fertilization (P1), chemical fertilization (P2), bio fertilizer every 2 weeks (P3) and bio fertilizer every 1 month (P4). The result showed that application of bio fertilizer every 2 weeks and 1 month can increase height, diameter and dry weight of cocoa seedlings on first until fourth months after fertilization. The Mycorrhizal Dependency (MD) of cocoa seedlings was classified as moderately dependent (27,04–45,86%). The highest colonization of arbuscular mycorrhizal fungi on roots cocoa resulted by P4 treatment about 33,92%.